Determining Factors for Discontinuing Hormonal Contraceptive Use in Acceptors at The Kassi Kassi Community Health Center - Nia Karuniawati; Rahmawati Ramli (Indonesian Socety of Obstetrics and Gynecology, 2026)
Introduction : During the COVID-19 pandemic, several experts have reported the effects of pregnancy accompanied by COVID-19 on both the mother and infant, influenced by the symptoms and signs presented. This study aims to analyze the correlation between blood markers; C-Reactive Protein (CRP), D-Dimer, Neutrophil-to-Lymphocyte Ratio (NLR) and the severity of COVID-19 in pregnant women during the 2020 pandemic at Persahabatan Hospital, Jakarta. Method : This cross-sectional study was conducted at Persahabatan Hospital, a National Respiratory Referral Center in Jakarta. A total of 525 pregnant women who met the inclusion criteria were evaluated. Laboratory markers, including CRP, D-Dimer, and NLR, were analyzed and categorized as normal or elevated. Data were analyzed using Chi-Square tests, and correlations were evaluated using Spearman’s rank correlation coefficient. Result : The result of this study found that elevated biomarkers were significantly correlated with increased severity of disease. CRP (>10 mg/L), D-Dimer (>3333 mg/L), and NLR (>5.8) were all associated with moderate to severe disease. Statistical analysis showed significant correlations with p-values <0.005 and a 95% confidence interval. Conclusion : Elevated CRP, D-Dimer, and NLR levels are associated with increased disease severity in pregnant women with COVID-19. These biomarkers can serve as useful predictors for the severity of the disease. Keywords : Covid 19, CRP, D-Dimer, NLR , Pregnant